In search of dialogue and discourse in applied clinical informatics - Kim, G. R.; Lehmann, C. U. (Applied Clinical Informatics, 2009)
We present a model of applied clinical informatics in the context of medical informatics in general, across the domain of health sciences and the continuum of information technology development and its adoption into workflow. The distinct challenges of applied clinical informatics present an opportunity to improve efforts through collaboration of the growing number of physicians, health institutional leaders and other health workers in successfully implementing working systems. This journal will be a forum for discussion regarding approaches to design, implement, deploy and evaluate systems and importantly, how to present experiences in a way to maximize sharing of those experiences.
Keywords: Medical Informatics Applications; Socio-technical aspect of information technology; Communications; Evaluation; Theoretical Models